Audits of antibiotic prescribing in a Bristol hospital. Issue 6359 (8th January 1983) - Swindell, P J; Reeves, D S; Bullock, D W; Davies, A J; Spence, C E
Abstract : Audits of antibiotic prescribing were done for periods of up to eight weeks in two successive years on medical, surgical, orthopaedic, gynaecology, obstetric, and urology wards and in an accident and emergency department. Clinical details were matched with antibiotic prescribing, and the appropriateness of the latter was judged independently by two medical microbiologists. Only when they agreed was an individual prescription included in the analysis. Overall, 28% of prescriptions in 1979 and 35% in 1980 were judged as unnecessary, with 17% and 16%, respectively, being for inappropriate choices of antibiotic. An educational programme about antibiotic prescribing carried out between the audits had no beneficial effect overall. Though the results compared favourably with those of audits published, prescribing could still be much improved. To judge by the failure of education, however, this might be difficult to achieve. Most prescriptions were written by junior staff, who in the absence of guidance from their seniors and because of their frequent moves would require a widespread and continual education programme. Published concern about the quality of antibiotic prescribing appears to be justified.